Disparities in Utilization of Social Determinants of Health Referrals Among Children in Immigrant Families - Uwemedimo, Omolara T.; May, Hanna (Frontiers in Pediatrics, 2018)
Objective: Children in immigrant families (CIF) are at elevated risk of experiencing adverse social determinants of health (SDH), particularly material hardship, which contribute to disparate health outcomes. Previous studies have found that SDH screening programs integrated into pediatric practices have increased receipt of social service resources. Few studies have examined use of social services in these programs among ethnically-diverse patient populations and associations with caregiver immigrant status or limited English proficiency (LEP). Methods: Caregivers of children (<18 years) were routinely screened in a practice-based, SDH screening program offering referral, assisted navigation and follow-up support. Information on caregiver race/ethnicity, US nativity, citizenship status and self-reported English proficiency was collected. Associations with utilization of referral resources at 12 weeks were measured using Chi-square and Fisher’s Exact tests. . Results: Of 148 caregivers, most were mothers (83.2%) and non-White (91.9%). Over half were born outside of the U.S (59.7%) and one-third were LEP (33.6%). Approximately one-third (30.9%) successfully utilized program-provided resources at 12-week follow-up. LEP caregivers and undocumented caregivers were more likely to be lost-to-follow-up. However, LEP caregivers who remained in the program utilized resources more than English-proficient caregivers (38.4% vs. 18.4%, p=0.031). Similarly, significantly more non-citizen caregivers utilized referrals compared to US citizens (37.4% vs. 23.1% vs. 0.0%, p=0.043). Conclusions: Families with non-US citizen or LEP caregivers were at highest risk of being lost-to-follow-up, but if engaged, were more likely to utilize resources. These findings indicate the need for larger studies to determine how to prevent loss-to-follow-up among immigrant and LEP caregivers participating in SDH screening programs.